Selection and Evaluation of Reference Genes for miRNA Expression Analysis in Bemisia tabaci Under Insecticide Tolerance - Zhang, Qinghe; Gao, Bingli; Qu, Cheng; Luo, Chen; Wang, Jinda; Wang, Ran (Frontiers in Genetics, 2022)
A growing number of studies are focused on microRNA (miRNA) expression in Bemisia tabaci, one devastating agricultural insect pest of tropical and subtropical areas for which the primary means of control are insecticides. In studying the genetic underpinnings of insecticide resistance, choice of stable reference genes for normalizing data plays key role to acquire unbiased expression profiles results from quantitative real-time PCR (qPCR) analysis. Expression profiles of eleven selected reference genes were determined systematically in B. tabaci exposure to eleven insecticides. Furthermore, we assessed stability of all the selected candidates in relation to other variables such including sex, tissue type, and developmental stage. Candidate reference gene validation was conducted by analyzing let-7-5p expression under various experimental treatments. Five programs including BestKeeper, NormFinder, geNorm, △Ct, and RefFinder were applied to verify accuracy of the selected candidates. Our results displayed that the best choice of the selected candidates for pymetrozine, sulfoxaflor, flonicamid, cyantraniliprole, afidopyropen, and deltamethrin treatment were miR-1-3p and miR-100-5p, U6 and miR-100-5p were best for chlorpyrifos and imidacloprid treatments, and U6 and miR-1-3p were best for flupyradifurone and β-cypermethrin treatments. The reference genes miR-624, miR-252, and miR-275 worked best in adult tissues, miR-100-5p and miR-1-3p worked best in either sex, and miR-624 and miR-11 were best to use across developmental stages. No one reference gene was found to be suitable for all experimental conditions. Our results contribute to the growing body of literature on qPCR reference gene selection under various experimental conditions and facilitates further investigations on gene expression changes in B. tabaci resulting from pesticide exposure.